Historical perspectives on organized crime and terrorism - Windle, James (Routledge SOLON explorations in crime and criminal justice histories, 2018)
Introduction: Hawking the historical method in organised crime and terrorism studies / James Windle, John F. Morrison, Aaron Winter and Andrew Silke. Organised crime -- "A citadel of crime" : Saint Paul, Minnesota, and the O'Connor system / James A. Densley -- The causes of traditional organized crime : comparing Chicago and New York / Robert M Lombardo -- The French connection : a brief critical history / Ryan Gingeras -- "He just wasn't the bloke i used to know" : social capital and the fragmentation of a British organised crime network / James Windle -- Terrorism -- 1975 : the truce that changed the troubles / John F. Morrison -- The Klan is history : a historical perspective on the revival of the far-right in "post-racial" America / Aaron Winter -- Terrorism and organised crime? -- Somali maritime predation : traditional piracy or a new form of terrorism? / Anamika Twyman-Ghoshal -- Narcoterrorism in Colombia / Francis Gaffney -- Empire, war, decolonisation and the birth of the illicit opium trade in Burma, 1800-1961 / John Collins -- Jamaat-al-Muslimeen : the blurred lines between organised crime and terrorism in Trinidad and Tobago / Andrew Silke